1990
DOI: 10.1113/jphysiol.1990.sp018216
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic‐parasympathetic interactions at the heart, possibly involving neuropeptide Y, in anaesthetized dogs.

Abstract: SUMMARY1. Stimulation of cardiac sympathetic nerves caused prolonged inhibition of vagal effects on heart rate, an effect which has been proposed on the basis of previous studies to be due to neuropeptide Y or a neuropeptide Y-like substance, released from the sympathetic nerves.2. This prolonged vagal inhibitory effect was attenuated or abolished when the sympathetic stimulation responsible was given together with continuous vagal stimulation.3. Continuous vagal stimulation alone did not modify the ability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 29 publications
3
8
0
Order By: Relevance
“…Neuropeptide Y released from sympathetic nerve terminals also interacts with ACh [8,11,47,48]. Conversely, the release of neuropeptide Y is prevented by simultaneous vagal stimulation [9,24]. As these studies have demonstrated mutually inhibitory prejunctional interactions, the phenomenon of bidirectional augmentation of dynamic heart rate regulation could not be directly explained.…”
Section: Prejunctional Mechanism Of Vago-sympathetic Interactionmentioning
confidence: 84%
“…Neuropeptide Y released from sympathetic nerve terminals also interacts with ACh [8,11,47,48]. Conversely, the release of neuropeptide Y is prevented by simultaneous vagal stimulation [9,24]. As these studies have demonstrated mutually inhibitory prejunctional interactions, the phenomenon of bidirectional augmentation of dynamic heart rate regulation could not be directly explained.…”
Section: Prejunctional Mechanism Of Vago-sympathetic Interactionmentioning
confidence: 84%
“…The complex patterns of co-localisation of NPY with other neurochemicals in intrinsic, nonsympathetic neurones in the heart, as well as in sympathetic nerves of extrinsic origin, serve as a basis for the various interactions and neuromodulatory roles of NPY at several, pre-and postjunctional sites in the heart (e.g. Potter 1987; Revington and McCloskey 1990;Gulbenkian et al 1992;Armour et al 1993;Rubino et al 1996). In addition, our observation of the close apposition of NPY-immunoreactive and non-immunoreactive varicosities in nerve bundles may represent sites of prejunctional modulation by NPY of the activity of neurones that do not contain NPY (see Gulbenkian et al 1992;Rubino et al 1996).…”
Section: Discussionmentioning
confidence: 98%
“…Intracardiac neurones are sensitive to NPY (Armour et al 1993), and so the presence of NPY-immunoreactive nerve profiles associated with these intrinsic neurones in ganglia may indicate that this is the site for postjunctional interactions between the sympathetic and parasympathetic innervation of the heart that are mediated by NPY (e.g. Potter 1987;Revington and McCloskey 1990). Another possibility is that the NPY-immunoreactive nerve profiles seen in the ganglia are the terminals of other intrinsic, intracardiac interneurones and therefore NPY may be involved in local neuronal reflexes (Ardell et al 1991;Saffrey et al 1992;Allen et al 1994;Murphy et al 1994a, b).…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] With regard to the neural control of the heart, a number of studies have shown that an antecedent period of intense sympathetic stimulation can profoundly and persistently attenuate the chronotropic responses to subsequent vagal test stimulations.10-16 This profound inhibition of vagal efficacy by antecedent sympathetic activity is believed to be mediated by the release of a specific neuropeptide from the sympathetic nerve endings; in the dog, the specific neuromodulator is neuropeptide Y (NPY). [10][11][12][13][14][15][16] When intense vagal stimulation is given concurrently with the sympathetic stimulation, however, the chronotropic responses to subsequent vagal test stimulations are no longer attenuated. 15 Thus, a period of intense sympathetic activity alone would be expected to abolish or attenuate vagal preponderance for a substantial time after cessation of the antecedent sympathetic activity.…”
Section: Sequence Of Excitation As a Factor Inmentioning
confidence: 95%
“…[10][11][12][13][14][15][16] When intense vagal stimulation is given concurrently with the sympathetic stimulation, however, the chronotropic responses to subsequent vagal test stimulations are no longer attenuated. 15 Thus, a period of intense sympathetic activity alone would be expected to abolish or attenuate vagal preponderance for a substantial time after cessation of the antecedent sympathetic activity. Conversely, an equivalent period of concurrent intense vagal and sympathetic activity would be expected to have only a negligible influence on subsequent vagal preponderance.…”
Section: Sequence Of Excitation As a Factor Inmentioning
confidence: 95%